Pengaruh Financial Knowledge Dan Socialization Agents Terhadap Management Behavior Pada Mahasiswa Universitas HKBP Nommensen Medan - Pardede, Wahyu K.; Manalu, Darma; Simangunsong, Ridhon NB. (Research and Community Service UNIVERSITAS KALBIS, 2025)
This research aims to determine the influence of Financial Knowledge and Socialization Agents on Financial Management Behavior in HKBP Nommensen University students. This research was conducted using quantitative methods. Data collection techniques using questionnaires. Based on hypothesis testing with the t test, the calculated t value for the Financial Knowledge variable is 4.754, where the value is > from t table 0.2006 and the significant value for the Financial Knowledge variable is 0.000 < from the significance level of 0.05 (5%). So it can be concluded, Financial Knowledge has a positive and significant effect on Financial Management Behavior. And the f test obtained a calculated f value of 11,733 where this value is > f table of 3.09. And the significant value is 0.000 < the significance level of 0.05. So it can be concluded that simultaneously Financial Knowledge and Socialization Agents together have a significant influence on Financial Management Behavior.